IMPLEMENTASI RANGE OF MOTION (ROM) AKTIF PADA LANSIA DENGAN RHEMATOID ARTRITIS (RA) YANG MENGALAMI NYERI SENDI EKSTREMITAS BAWAH DI UPT PELAYANAN SOSIAL LANJUT USIA BINJAI - Winda Wulandari Sembiring; Muchti Yuda Pratama; Nina Olivia (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
Rheumatoid arthritis (RA)is an autoimmune disease that causes inflammation ana pain in the joints, particularly in the lower extremities. Active range of motion (ROM)is a physiotherapy intervention that can help improve mobiliry and reduce joint pain. ROM movements can enhance blood circulation to the joint capsule and increase joint flexibility, thereby reducing or even eliminating pain and improving physical mobility. This study aims to implement active ROM exercises in elderly individuals experiencing joint pain in the lower extremities. The research employed a descriptive method in the form of a scientific care approach, starting a from evaluation. The mild 10 ROM paper using nursing assessment, diagnosis,intervention .implementation,to subjects were two elderly individuals experiencing moderate joint pain in the lower extremities.Active exercises were implemented for 15 minutes, twice a day,over a period of 6 days. The results showed a reduction in pain scale from moderate to mild after administering ROM exercises to both subjects for 6 days. The implementation ofROM exercises should be carried out continuously.along with the development of standard operating procedures for ROM exercises in RA patients experiencing lower extremity joint pain.